INTERACTION OF CO2 AND LIGHT AVAILABILITY ON PHOTOPHYSIOLOGY OF TROPICAL COCCOLITOPHORIDS (EMILIANIA HUXLEYI, GEPHYROCAPSA OCEANICA, AND OCHOSPHAERA SP.) - Nita Rukminasari; Muhammad Lukman; Khusnul Yaqin (Universitas Medan Area, 2023)
The study to examine the calcification rate, adaptation, and the biotic response of three tropical coccolithophorids (Emiliania huxleyi, Gephyrocapsa oceanica, and Ochosphaera sp) to changes in CO2 concentration. Three selected calcifying coccolitophorids were grown at batch culture with CO2 system at two levels of CO2 (385 and 1000 ppm) and two light dark periods. The parameters measured and calculation including growth rate, particulate organic carbon content, particulate inorganic carbon content, chlorophyll a, cell size, photosynthetic, organic, inorganic carbon production, photosynthesis, and calcification rate. The results showed that there was a different response to carbonate chemistry changes and dark and light periods in any of the analyzed parameters. The growth rate of three selected calcifying microalgae tested was decreasing significantly at high concentrations of CO2 (1000 ppm) treatment on 14:10 hour light: dark periods. However, there was no significant difference between the two CO2 concentrations where they were illuminated by 24 hours light in growth rate. The increasing CO2 concentration and light-dark periods were species-specific responses to photosynthesis and calcification rate for three selected calcifying microalgae.